Features of diagnosing postexertional malaise and chronic fatigue syndrome in the development of medical rehabilitation programs for long COVID - Ksenia S. Avdeeva; Tatiana I. Petelina; Aleksandr V. Gorbachevskii; Yliya A. Sharoyan; Marina I. Bessonova (КардиоСоматика)
One of the key challenges in modern medical rehabilitation is the recovery of patients with symptoms of long COVID. Various types of physical exercise are considered the most effective rehabilitation methods. However, according to published data, there is a phenotype of long COVID associated with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), characterized by postexertional malaise and exercise intolerance. For safe medical rehabilitation, early identification of ME/CFS and the development of alternative rehabilitation programs with reduced physical exertion are required for this category of patients.